Genetic variability for clonal selection in Java citronella (Cymbopogon winterianus Jowitt.) - Lal, R K (Journal of Spices and Aromatic Crops, 2002)
Java citronella (Cymbopogon winterianus Jowitt.) grass is one of the important aromatic plants of South Asia. Its oil is used extensively as a source of important perfumery chemicals. The nature and amount of genetic variability and stability factor, among 34 diverse accessions of Java citronella assembled from different states of India and Sri Lanka were estimated based on 14 quantitative and qualitative traits. The heritability in broad sense (h2 BS %) was generally high for all the traits (91.02 - 98.96%). However, it was medium for leaf length (71.40%) and plant height (71.61%) and low for citronellal content (10.65%) and oil yield (40.57 %). Generally clones were highly unstable for elernol content (SPi = 28.67), followed by herb yield (SPi = 14.67), oil yield (SFi = 10.50), citronellal content (SPi = 8.18), citronellol content (SFi = 7.20), gerenyl acetate (SPi = 3.77), tillers planrl (SFi = 3.47) and geraniol content (SPi = 3.07). However, leaf width (SFi = 1.68) and leaf length (SPi = 1.85) were found stable to some extent. The plant height (SPi 2.31) followed by lilnonene content (SPi = 2.4), oil content (SFi = 2.6) and citronellyI acetate (SFi = 2.96) were moderately stable. Based on the magnitude of stability factors and different genetic parameters, clone Nos. 10, 20 and 3 for high biomass; 28, 30 and 2 for high oil and I, 9 and 12 for high oil and citronellol content were identified for commercial exploitation.